Lemon Butterfly - Cao, Wenxuan 1954-; Mello, Roger (New York, NY : Reycraft Books, 2020)
"A lemon butterfly is searching for the most beautiful thing in the world--a field of flowers. Through barren wilds, across a wide river, and over a bald mountain the butterfly continues the search until its final miraculous transformation."--Provided by publisher.
Keywords: Butterflies -- Juvenile fiction; Flowers -- Juvenile fiction; Butterflies -- Fiction; Flowers -- Fiction